Understanding and overcoming the sticking point in resistance exercise - Kompf, J.; Arandjelovic, O. (Sports Medicine, 2016)
In the context of resistance training the so-called "sticking point" is commonly understood as the position in a lift in which a disproportionately large increase in the difficulty to continue the lift is experienced. If the lift is taken to the point of momentary muscular failure, the sticking point is usually where the failure occurs. Hence the sticking point is associated with an increased chance of exercise form deterioration or breakdown. Understanding the mechanisms that lead to the occurrence of sticking points as well as different training strategies that can be used to overcome them is important to strength practitioners (trainees and coaches alike) and instrumental for the avoidance of injury and continued progress. In this article we survey and consolidate the body of existing research on the topic: we discuss different definitions of the sticking point adopted in the literature and propose a more precise definition, describe different muscular and biomechanical aspects that give rise to sticking points, and review the effectiveness of different training modalities used to address them.